Using Intervention Mapping to Develop and Adapt Two Educational Interventions for Parents to Increase HPV Vaccination Among Hispanic Adolescents - Rodriguez, Serena A.; Roncancio, Angelica M.; Savas, Lara S.; Lopez, Diana M.; Vernon, Sally W.; Fernandez, Maria E. (Frontiers in Public Health, 2018)
Introduction: Effective interventions to increase HPV vaccination are needed to reach national vaccination goals and to reduce later HPV-related cancer disparities. We used Intervention Mapping (IM) to develop and adapt a theory- and evidence-based educational intervention targeting parents of Hispanic adolescents to increase HPV vaccination. Methods: We followed IM Steps 1-6 to: 1) develop a logic model and identify modifiable factors associated with vaccination among Hispanic adolescents by conducting literature reviews, focus groups, and in-depth interviews with Hispanic parents; 2) develop outcomes, write performance objectives, and develop a matrix of change objectives; 3) develop and identify a program theme, program components, theoretical methods, and practical applications; 4) develop an intervention design plan; 5) develop implementation strategies; and 6) develop an evaluation plan. We completed Steps 1-6 for to develop an intervention targeting parents of females, and we followed the steps again to adapt the program once HPV vaccine recommendations included males. Results: The program Por Nuestras Hijas (For Our Daughters) included two components: a print fotonovela and a tailored interactive multimedia intervention (TIMI). The program utilized the methods tailoring, targeting, framing, anticipated regret, modeling, skill building, and education and counseling to target the following determinants: parental knowledge, attitudes, self-efficacy, skills, perceived benefits/barriers, perceived susceptibility, perceived norms, and outcome expectations as modifiable factors influencing HPV vaccination. Lay health workers implemented the program in community clinics. A logic model of change guided evaluation planning. We later adapted the outcome and intervention content for parents of Hispanic adolescent males and changed the theme to Por Nuestros Hijos (For Our Children). Throughout the development and adaptation processes, we relied on theory, empirical evidence, and new data to make decisions. Discussion: IM provided a systematic methodology for program development and adaptation. Tasks in each step built upon one another integrating findings from the literature, previous research, qualitative findings, and theory to develop two educational programs for parents to increase HPV vaccination. The systematic process allowed us to develop messages and materials targeting factors beyond HPV knowledge or awareness to create behavior change.